CITRA WANITA TOKOH UTAMA DALAM NOVEL “TARIAN BUMI”KARYA OKARUSMINI KAJIAN FEMINISME LIBERAL - Anita Eka Syalina; Eko Cahyo Prawoto (Buana Bastra, 2020)
This study aims to describe and explain (1) Self-image in Oka Rusmini's Earth Dance Novel (2) Social Image in Oka Rusmini's Earth Dance Novel. This research uses a study of Liberal Feminism. The approach used in this research is descriptive qualitative research. The data in this study are in the form of words, sentences in th e form of expressions, and dialogues between characters that show self-image and social images which are the focus of research. The data source in this study is the novel Tarian Bumi by Oka Rusmini. Data collection techniques in this study used the observation and note technique. The results of this study are able to explain the image of the main female character which includes self-image, and the social image that is owned by the main character of Balinese women. Through Oka Rusmini's novel Tarian Bumi, it explains the struggles of women and the conflicting rules in the family that makes one of the main characters, Ida Ayu Telaga Pidada, willing to leave her national title because she doesn't want to follow her mother's wishes. Telaga's rejection of the mother caused the relationship between mother and child to break up. Telaga who eventually left her family and became a complete Sudra woman even though she always had different opinions with her in-laws.